Two novel myxosporean parasite species of Ceratomyxa Thélohan, 1892 from the banded cusk-eel Raneya brasiliensis (Kaup) (Ophidiiformes: Ophidiidae) off Patagonia, Argentina - Alama-Bermejo, Gema; Hernández-Orts, Jesús S; Huchon, Dorothée; Atkinson, Stephen D (Parasitology international, 2021)
We described two novel myxozoan parasite species Ceratomyxa argentina n. sp. and Ceratomyxa raneyae n. sp. from the gall bladder of Raneya brasiliensis (Kaup) from the Patagonian coast of Argentina. Both species can be distinguished from other ceratomyxids by myxospore and polar capsule (nematocyst) morphology and morphometry, fish host and geographic locality. Phylogenetic reconstruction using ssrDNA gene sequences showed that the two new species are placed in a long-branching ceratomyxid clade which also include Ceratomyxa appendiculata Thélohan, 1892, Ceratomyxa anko Freeman, Yokoyama and Ogawa, 2008, Ceratomyxa pantherini Gunter, Burger and Adlard, 2010 and Pseudoalataspora kovalevae Kalavati, MacKenzie, Collins, Hemmingsen and Brickle, 2013. This study documents additional biodiversity of marine myxozoans in the South Atlantic, a region still largely unexplored for this group of parasitic cnidarians.
Keywords: Parasitic Diseases, Animal; parazitární nemoci u zvířat; Southwestern Atlantic; Fish Diseases; Fishes; ssrDNA; Marine clade; zvířata; Taxonomy; ryby; nemoci ryb; Argentina; Myxozoa; fylogeneze; Phylogeny; Animals